JOB SATISFACTION FACTORS OF SHOES FACTORY STAFFS - Theodosia C. Nathalia; Yustisia Kristiana (Universitas Gunadarma, 2012)
Job satisfaction plays an important role on the work performance of employee. when an employee are satisfied in the work then an employee will do everything possible with all the skills to complete the task, which will eventually produce a good performance and achievement for the company. The object in this study was employees of shoes factory located in Balaraja, Tangerang. The number of employees totaled 10.600 people, but the study sample only 414 people using the convenience sampling technique. Determinant of job satisfaction used in this study is the opportunity for advancement, job security, working conditions, compensation, promotion, supervision, coworkers, and management companies. Analysis used in this research is descriptive analysis. In descriptive analysis, this value can be represented either by the mean. The results indicate that employees are satisfied with job security. Finally, provide input to the factors of job satisfaction that results are less good.Key Words : job satisfaction, determinants of job satisfaction, job performance